NILAI KARAKTER MODERAT DALAM CERITA RAKYAT BATURRADEN DAN IMPLEMENTASINYA DALAM PEMBELAJARAN SASTRA DI SEKOLAH MENENGAH ATAS (SMA) - Aryana Maula; Abdul Mukhlis (Pendidikan Bahasa dan Sastra Indonesia, 2025)
The Baturraden legend, as an integral part of Indonesia's cultural heritage, contains moral and ethical teachings relevant to the values of religious moderation, such as national commitment, anti-violence, tolerance, and accommodation toward local cultures. The importance of instilling these values in the younger generation aims to shape inclusive and tolerant character. This research aims to identify and analyze the values of religious moderation within the Baturraden legend and explore opportunities for its implementation in literature education at the high school level. The method used is descriptive qualitative research with content and interpretative analysis of the narratives and characters within the legend. The results of the study indicate that the Baturraden legend contains values of religious moderation that can be utilized as teaching materials in the literature curriculum, enhancing students' understanding of cultural diversity and fostering inclusive and tolerant character.